LATERAL DISTRIBUTION OF SANDSTONE MATURITY IN LOWER PART OF SUBMARINE FAN CHANNEL: A STUDY CASE FROM SEMILIR FORMATION, BANTUL DISTRICT, SPECIAL REGENCY OF YOGYAKARTA, INDONESIA - Bima Eko Dhanu, Bima Eko Dhanu (Departmen Teknik Geologi, 2015)
Submarine fan channel is one of highly prolific reservoir in Indonesia, such as deeper Kutai Basin in Makassar Strait. Compare to common fluvial channel system, lateral distribution of maturity as well as may due to turbidity system. In this maturity have more complex study, model of lateral distribution of submarine fan channel, especially in lower part, is proposed to reveal the complexity of this system. Data was collected from single channel sand body in Semilir Formation which is located in Piyungan Subdistrict. The study was conducted in single layer which is affirmed has relation horizontally, then we conducted analysis of mineralogy to get major minerals data, such as quartz, feldspar, matrix abundant of thin sections petrographically and also grain size by handy observation. The result of this study was expected to inform us that there are maturity trend related to major minerals (quartz, feldspar, matrix). The study is important for petroleum industry to enhance target in searching good maturity of sandstone reservoir body and also could be optimize hydrocarbon production in the field